Uncoupling American empire : cultural politics of deviance and unequal difference, 1890-1910 - Cho, Yu-Fang, 1974- (SUNY series in multiethnic literature, 2013)
"A cultural studies consideration of marriage and those considered "deviant" in the nineteenth-century American imagination"--Provided by publisher.